(untitled) (Research, Society and Development, 2020)
The present work aimed to perform the drying kinetics of shelled walnuts at different drying air temperatures and to adjust different mathematical models to experimental drying data, selecting the one that best describes the phenomenon. The drying kinetics were performed in a dryer with air circulation with an air speed of 1.5 m/s, at temperatures of 40, 50 and 60 °C. The experimental data were adjusted using the empirical models of Page, Handerson and Pabis, Newton, Logarithmic and Midili. The best model was selected taking as a parameter the magnitude of the coefficient of determination (R2) and the mean square deviation (DQM). The Page and Midili models stood out from the others because they presented the best R2 values (> 99%) and the lowest DQM values (<0.0306463) for the studied drying temperatures. The drying kinetics of the nuts without shells showed that the temperature was the variable of greatest influence in the process, and that the drying constant “k” increased with its increase, and the time of the process decreased due to its increase.